A desnutrição e o transitivismo: considerações psicanalíticas - Dauer, Érika Teles (2015)
The topic of this study is the symptoms of infantile orality, especially the barriers to feeding that lead to the symptom of malnutrition. Through psychoanalytical interventions with malnourished children served by the First Infancy Institute (Iprede), this study addresses what is in play in infantile feeding symptomatic productions. Considering that malnutrition is influenced by the relationship between the child and his or her primary caregiver – a relationship that reflects specific styles of maternal ties – this study was conducted based on the concept of transitivism. Given this baseline, the study’s objective was to understand the feeding problems of infancy and relate those problems to maternal transitivism, focusing on the academic productions of Jean Bergès and Gabriel Balbo. The primary methods used to achieve said objective were examination of existing research and case studies. First, according to the orientations of Freud and Lacan, a study was conducted about the role that feeding plays in the creation of the psychic self, emphasizing the privileged role that food occupies in the primitive processes of exchange in the mother-child relationship. Next, the study analyzed transitivism, considering the operation of the supposition of the subject and the establishment of demand. Finally, from the clinical case studies, this study attempted to weave together the possible relationships between the symptom of food refusal, maternal narcissism, and the barriers revealed in the transitive operation. The results of this study point to the psychic determiners of malnutrition, particularly those related to the barriers to maternal function. The symptom of malnutrition can cause displacement in orality, from difficulties with weaning to difficulties with verbal language, superseding the original problem. Transitivism is a concept that is pertinent to this study because it deals with the subjective position of and ties between mother and child. Because psychoanalysis allows for a view broader than generalizations, it has much to contribute to the understanding and problem solving of infantile feeding symptoms, contributing, in turn, to institutional clinical work.